The level of science teachers' practice of productive thinking skills From the point of view of school principals and subject supervisor (Journal of Misan Researches, 2024)
The current research aims to know the level of science teachers' practice of productive thinking skills, and to achieve the goal of the research; The researchers followed the descriptive approach (work analysis) The research sample consisted of (153) principals and educational supervisors who were randomly selected from Misan Governorate. The researchers prepared a closed questionnaire that included (28) A paragraph divided into five axes (fluency, flexibility, originality, interpretation, conclusion, and to treat the data statistically, the researchers used Chi-square, Pearson correlation coefficient, split-half, Spearman-Brown equation, Facronbach equation, weighted means and standard deviations The current research found that the level of science teachers' practice of productive thinking skills was moderately This result is not the desired level for training learners to practice productive thinking skills at an advanced level.